Antibacterial activity and mechanism of slightly acidic electrolyzed water against Shewanella putrefaciens and Staphylococcus saprophytic - Liu, Lin; Lan, Weiqing; Wang, Yanbo; Xie, Jing (Biochemical and biophysical research communications, 2022)
The purpose of this study was to investigate the antimicrobial effect and mechanism of slightly acidic electrolyzed water (SAEW) against Shewanella putrefaciens (S. putrefaciens) and Staphylococcus saprophytic (S. saprophyticus). The results showed that SAEW exhibited strong antimicrobial activity against tested bacteria, which was positively correlated to the available chlorine concentration (ACC) of SAEW. The mortality rate of S. putrefaciens and S. saprophyticus was up to 96% and 85%, respectively, when the ACC of SAEW was 60.0 mg/L. The results of scanning electron microscopy (SEM) showed that the cell morphology and structure were destroyed by SAEW. Besides, the results of confocal laser scanning microscopy (CLSM), leakage of DNA and protein provided evidence that SAEW induced membrane permeabilization in cells. Compared with the control, the intracellular reactive oxygen species (ROS) generated by SAEW was strengthened significantly with the increase of ACC, and the cells were injured to death accordingly. [Display omitted] •SAEW exhibited a strong bactericidal ability against fish spoilage bacteria.•SAEW treatment could cause damage to the cell structure.•The release of ROS induced the necrosis of cells after SAEW treatment.•Intracellular antioxidant enzyme activity decreased after SAEW treatment.